Filles et fils au prisme des journaux d’observation rédigés par leurs parents (Suisse romande, 1780-1820) - Sylvie Moret Petrini (Genre & Histoire)
Based on thirteen educational or observational diaries kept by middle-class parents from the French-speaking part of Switzerland between 1780 and 1820, this article analyses this writing practice and the way the writers speak about their children. And it starts from the very moment of birth and the announcement of the child's sex. These descriptions allow us to question the influence of feminine and masculine representations on the way that fathers and mothers observe their offspring, which is intended to be scientific, and this at a time when child observation was becoming an educational issue for Enlightenment educators and philosophers. The descriptions also appear to be influenced by the staging of the diarist's own role, as father or mother, and his or her expectations of that role.